Surgical Emergencies in the Cancer Patient - Fong, Yuman; Kauffmann, Rondi Marie; Marcinkowski, Emily; Singh, Gagandeep; Schoellhammer, Hans F. (Springer International Publishing : Imprint: Springer, 2017)
This text provides a comprehensive textbook summarizing the presentation, workup, and surgical solutions for common emergencies in the cancer patient. The use of medications (antibiotics, hormones, and biologic therapies) and interventional radiologic procedures as adjuncts or as replacements for the surgical solutions are discussed. The text covers emergencies that result as adverse effects for the systemic and local treatments for cancer, emergencies that result from mechanical issues with the cancer and those that result from surviving major extirpative surgery. Diagnosis and treatment of patients' immune-compromised or thrombocytopenic status from chemotherapy is discussed, as is surgical treatment in patients with prior complex surgical therapy or radiation treatment. Finally, the text covers alternatives to surgery, including new interventional radiologic and endoscopic procedures. Surgical Emergencies in the Cancer Patient will be of great value to healthcare professionals at all levels who are involved in the treatment of emergencies in the cancer patient. It is meant for a wide group of individuals, including medical students, residents in surgery and internal medicine, fellows in surgery and oncology, and practicing oncologists and surgeons. This work is meant to be a textbook for the student, a guide for the practitioner, and a reference for the general oncologist.
Keywords: Medicine.; Oncology.; Surgery.; Surgical oncology.; elektronické knihy; electronic books